2019
DOI: 10.1186/s12967-019-1827-1
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome screening using culture medium of embryos fertilised in vitro: a pilot clinical study

Abstract: Background Previous studies from this as well as other research groups suggested that non-invasive chromosome screening (NICS) with embryo culture medium can be used to identify chromosomal ploidy and chromosomal abnormalities. We here report a series of clinical cases utilizing the technology. Methods A total of 45 couples underwent in vitro fertilisation during a period between February 2016 and February 2017. Karyotyping revealed normal chromosomes in both partners i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 33 publications
1
37
0
1
Order By: Relevance
“…While none of them provided encouraging results, two showed that TE-biopsy PGT-A was superior to niPGT-A (28,30). However, one very recent study in women <30 y reported 27 normal births following transfer of 50 embryos identified as euploid by niPGT-A (31). Moreover, in another report, when combining niPGT-A with blastocoel fluid DNA analysis, concordance was higher than PGT-A with TE biopsy alone (29).…”
Section: Significancementioning
confidence: 99%
“…While none of them provided encouraging results, two showed that TE-biopsy PGT-A was superior to niPGT-A (28,30). However, one very recent study in women <30 y reported 27 normal births following transfer of 50 embryos identified as euploid by niPGT-A (31). Moreover, in another report, when combining niPGT-A with blastocoel fluid DNA analysis, concordance was higher than PGT-A with TE biopsy alone (29).…”
Section: Significancementioning
confidence: 99%
“…Results were fully concordant when SCM-PGT was compared with pregnancies (Galluzzi et al, 2015) or live births . Moreover, a recent study reported 27 healthy births after SCM-PGT (Fang et al, 2019). Although encouraging, these results do not allow any conclusion to be reached because the number of cases is too low.…”
Section: Reliability Of Non-invasive Preimplantation Genetic Testing mentioning
confidence: 92%
“…Only later studies revealed that maternal DNA contamination from the oocyte retrieval procedure is a significant concern, and the uninterrupted culture from zygote to blastocyst stage likely maximizes that problem. The same testing method, namely MALBAC amplification (Yikon Genomics) and NGS on a HiSeq 2500 instrument (Illumina), was used in a study by Fang and colleagues, this time washing embryos at Day 3 of culture and moving to new media drops until Day 5 or 6 [223]. The study reports a 97% amplification rate in the 170 samples analyzed.…”
Section: The Prospect Of Non-invasive Pgt-amentioning
confidence: 99%